Quality of life and its associated factors among elderly people of Kanchan Rup Municipality in province 2: A community-based study. - Gupta, Bimala Kumari Sah
ABSTRACT: Introduction: Over a decade, the life expectancy of people is increasing and rapid the number of ageing population. Quality of life of elderly people is a neglected issue, especially in developing countries, including Nepal. This study aimed to assess the QOL and its associated factors among the elderly people of Kanchan Rup Municipality, Province 2. Methods: A community‑based cross‑sectional study was conducted among 216 participants (aged 60 years and above) selected using simple random sampling from Kanchan Rup Municipality from April to July 2021. A structured questionnaire was used to collect data on sociodemographic characteristics, self‑reported health problems and QOL-35. Data analysis were performed using SPSS version 20.0. Ethical approval was taken from NHRC. Descriptive statistics (frequency, percentage, mean, SD) and inferential statistics (independent t-test, one way ANOVA) were used for data analysis at 5% of level of significance. Results: The study found that 52.8% elderly has quality of life score below mean score. The average quality of life score was 3.34±0.55 ranging from 1.37 to 4.89 in scale of 5. The elderly had a comparatively good quality of life based on home and neighbourhood (3.86±1.13) followed by social relationship (3.83±0.74), leisure activities (3.58±0.96), Psychological and emotional wellbeing (3.31±0.95) and Sense of Independence (3.17±0.59). However, the elderly quality of life is poor in terms of financial circumstances (2.5±0.64) and health (2.73±0.46) perspectives. Similarly Quality of life of participants (elderly) has significant differences in term of sex (p-value: 0.032), ethnicity (p-value: 0.014), Type of family (p-value<0.001), number of family members (p-value: 0.017), occupational status (p-value: 0.007) and with whom elderly are living with (p-value: 0.004) statistically at 95% confidence level. Also significantly related to existing health problems in elderly (p-value<0.001) at 95% confidence level. Conclusion: Based on the findings of the study it is concluded that quality of life of elderly people is below mean score. The elderly quality of life is poor in terms of financial circumstances and health perspectives. So it is strongly recommended for improve the supplemental security income program, increase the availability of programs that provideelderly benefits with healthcare and long-term care costs. Local government and health organization need to run screening program especially for promoting elderly health, also need to push for federal support for the long-term financial benefit and maintaining better health of elderly people of Kanchan Rup Municipality. Keywords: Quality of life, Associated factors, Elderly people, Community based study